Progress and Prospects of Research Ideas and Methods in the Network Pharmacology of Traditional Chinese Medicine - Zhongzhu Yuan; Yingying Pan; Tian Leng; Yu Chu; Haojie Zhang; Jingru Ma; Xiaoju Ma (Frontiers Media S.A., 2022)
In recent years, the emerging network pharmacology has been extensively applied to the field of traditional Chinese medicine and has made great contributions to the modernization of TCM. Therefore, this paper provides an overview of the progress of research ideas and methods in the network pharmacology in the last few years in the field of traditional Chinese medicine and presents insights into future research methods and ideas in the network pharmacology. Problems with the current network pharmacology are discussed and prospects of its future development are put forward.